2023
DOI: 10.3329/bmrcb.v49i1.62698
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated with Breakfast Skipping among Undergraduate Medical Students of a Selected Medical College in Bangladesh

Abstract: Background: Breakfast is a commonly skipped meal especially for young adult during their university study period. Objective: This study aimed to determine the factors related to skipping breakfast among medical students in this study. Methods: This cross-sectional study was conducted among the 4th year medical students of Sher-e-Bangla Medical College, Barishal in January 2022 using a self-administered questionnaire recording the demography, breakfast consumption habits, and other factors like physical conditi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
3
2

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(6 citation statements)
references
References 29 publications
1
3
2
Order By: Relevance
“…Congruent to the findings from previous studies among urban adults in Bangladesh [ 12 ], university professionals in Bangladesh [ 29 ] and among public sector medical institutes in Karachi, Pakistan [ 30 ], this study found that females were more likely to skip breakfast compared to their male counterparts. This finding is however not on par with findings from previous studies conducted among undergraduate medical students in Bangladesh [ 13 ] and among Inner Mongolia medical students in China [ 25 ]. The plausible reason for females having higher odds of skipping breakfast than males could be because females are more concerned about their body shape or body image and some may adopt skipping breakfast as a means to lose weight [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
See 4 more Smart Citations
“…Congruent to the findings from previous studies among urban adults in Bangladesh [ 12 ], university professionals in Bangladesh [ 29 ] and among public sector medical institutes in Karachi, Pakistan [ 30 ], this study found that females were more likely to skip breakfast compared to their male counterparts. This finding is however not on par with findings from previous studies conducted among undergraduate medical students in Bangladesh [ 13 ] and among Inner Mongolia medical students in China [ 25 ]. The plausible reason for females having higher odds of skipping breakfast than males could be because females are more concerned about their body shape or body image and some may adopt skipping breakfast as a means to lose weight [ 13 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A high prevalence of skipping breakfast (63.5%) among university students was observed in this study. This aligns with a previous study of 4th year medical students in Bangladesh [ 13 ], and is at the higher end of a range of estimates reported by additional studies investigating young adults [ 10 ] and urban-living adults [ 12 ]. In comparison to other countries, the prevalence recorded in this study is higher than 56.1% reported among university students in Malaysia [ 23 ], 55.4% reported among final year university medical students in Sri Lanka [ 24 ] and 28.9% also among university medical students in China [ 25 ].…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations